About philosophy of М.К. Mamardashvily (Journal of Philosophy Culture and Political Science, 2019)
Author of paper substantiates the unity of scientiﬁ c, philosophical and social-political aspects of philosophical views of well-known philosopher of soviet period М.К. Mamardashvily. Author reveals the philosophy of Mamardashvily within the context of problems of conciseness and thinking as original philosophical-anthropological concept. She reveals the importance of philosophy of Plato, Descartes, Kant, Marx, Husserl and Proust for Mamardashvily. Also, author presents the philosophy of Mamardashvily as speciﬁ c thinking space, in which Mamardashvily explained his philosophical position on many urgent issues of modern society from laws of thinking.